Offline version of the Proceedings of 15th EWTEC 2023, Bilbao (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Please note: this is a snapshot of the Proceedings of the 15th EWTEC made on 2023-10-01 and provided for convenience as a single download for offline use. The definitive version of the EWTEC Proceedings is the online version. To extract the files, use 7-Zip.